2020
DOI: 10.22159/ajpcr.2020.v13i7.37906
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Renal Dimensions and Glomerular Filtration Rate With Height, Weight, Body Mass Index, and Body Surface Area in Children

Abstract: Objective: The objective of the study was to estimate glomerular filtration rate (eGFR) and renal dimension and establish a correlation with age, weight, height, body mass index (BMI), and body surface area (BSA) of children and to measure renal dimensions (craniocaudal length, anteroposterior length, and transverse length) of both kidneys of 1–10 years children. Methods: A total of 500 children from 1 to 10 years old were screened by ultrasonography to measure renal craniocaudal length, anteroposterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…BSA, which is calculated based on weight and height, has been proven to correlate well with kidney volume. [11][12][13][14] Thus, a small number of large studies have investigated whether the relation between donor and recipient size, expressed using BSA, has an impact on renal transplant outcomes. All these included adult recipients [15][16][17][18] but two, one that included adolescent recipients 24 and one that included both adult and pediatric recipients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…BSA, which is calculated based on weight and height, has been proven to correlate well with kidney volume. [11][12][13][14] Thus, a small number of large studies have investigated whether the relation between donor and recipient size, expressed using BSA, has an impact on renal transplant outcomes. All these included adult recipients [15][16][17][18] but two, one that included adolescent recipients 24 and one that included both adult and pediatric recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown an association between kidney size and various anthropometric parameters, such as weight, height, body mass index (BMI) and BSA. BSA, which is calculated based on weight and height, has been proven to correlate well with kidney volume 11–14 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations